Decision Support System Algorithm for the Beneficiary of Uninhabitable Housing Funds - Diena Rauda, Ramdania; Subaeki, B; L., Muliawaty; M. A, Ramdhani (2021)
Poverty is one of the big problems facing the people of Indonesia. This problem evidenced by the existence of 3.4 million Indonesians living in settlements that are not livable. This problem is also a concern of the government by providing financial assistance for homes that are not livable. But in reality, the available aid is often not on target, not on a budget, and not on time. The purpose of this research is to implement the El Choination El Choix Traduisant La Realite (ELECTRE) algorithm as a decision support system to provide recommendations for potential recipients who deserve assistance from the government. System testing is done by inputting 46 prospective beneficiary data with predetermined criteria. The results showed the ELECTRE algorithm was able to provide recommendations with an accuracy rate of 86.9%. This result indicates that the decision support system using the ELECTRE method can use as an alternative to the efficiency of determining the prospective beneficiaries of uninhabitable housing in Indonesia.